Climate change adaptation policies in Bangladesh: gap analysis through a gender lens - Sharif, Ibrat; Nasir, Naznin; Khanum, Roufa; Khan, A S Moniruzzaman (© 2016 Published by BRAC University, 2017)
This article was published in the BRAC University Journal [© 2016 Published by BRAC University].